Trabalho e qualidade de vida: representações sociais do enfermeiro docente - Conceição, Maria Rodrigues da (2010)
Teaching has been studied through the relation of the docent practices with the educational institutions, in order to detect occupational deaseases usually found on docent’s job. This study has intended to ackknowledge the nurses’social representations related to their docent job and life quality, as well as comparing the docent nurses’ social representations at private and public institutions, attending to a descriptive and exploratory method, quantitatively and qualitatively. It was developed from March to June of 2010, based on Serge Moscovici’s social representations theory, and approved by the Ethics and Research Committee under register nº 05/2010. The data were collected from preformed personal informations, the Whoqol – brief, a questionnaire with twenty-six questions, the TALP, abbreviation for a free words’ association technique, where the main themes were work, life quality (in general) and life quality in particular (itself). It was also included a written narrative about the decision to work with teaching. The research was made with a total of thirty-eight docent nurses; thirty-seven women and one man. Thirty of them were married, six singles and two divorcée. Forty-six year old was the average of their age; all professors at graduate and postgraduate educational institutions: one private institution and two public - State and Federal – ones. The results were presented in six tables and three boards showed in absolute and percentage numbers with descriptive statistics. Narratives of fifteen docent nurses were chosen randomly focused on four categories: life quality and docent practices on graduating education, life quality and docent practices on post graduating education, enjoyment, and publications. By analyzing the tables three to six, it was observed that over physical and psychological qualities the sum of the percentage scores nothing / very poor / very dissatisfied, very little or not satisfied, more or less / medium didn’t show significant differences, whereas to the first was forty-seven percent (47%) and forty-three decimal four percent (43,4%) to the second; however, to the social relationships and environment domains we had twenty-two decimal two percent (22,2%) and thirty decimal six percent (30,6%) respectively. It was inferred that social representations of the three groups over the study were anchored by the words responsibility, commitment, money and enjoyment. General life quality was anchored by the words peace and health, and particular life quality was anchored by the words health, family, work and time. The data triangulation has allowed us to understand the significance of the docent nurse’s social representations, the complementarities to the findings by the different methods.